Exendin-4 as a Versatile Therapeutic Agent for the Amelioration of Diabetic Changes - Hadi Rajabi; Mahdi Ahmadi; Somayeh Aslani; Shirin Saberianpour; Reza Rahbarghazi (Tabriz University of Medical Sciences, 2022)
Type 2 diabetes mellitus (T2DM) is a chronic metabolic abnormality leading to microvascular and macrovascular complications. Non-insulin Incretin mimic synthetic peptide exendin-4 was introduced as an anti-diabetic drug which helped diabetic patients with triggering insulin secretion; further researches have revealed an effective role of exendin-4 in treatment of T2DM related diseases. Exendin-4 is approximately similar to Glucagon-like peptide, thus it can bind to the glucagon-like peptide-1 receptor (GLP-1R) and activated different signaling pathways that are involved in various bioactivities such as apoptosis, insulin secretion and inactivation of microglial. In this review, we investigated the interesting role of exendin-4 in various kinds of T2DM related disorders through the activation of different signaling pathways.